Blockchain and the Journey Beyond Double Entry. Issue 2 (20th November 2018) - Carlin, Tyrone
Abstract: Whilst blockchain technology has attracted substantial attention within the scholarly literature of a number of disciplines, including economics, finance, law and technology, it has been subject to minimal discussion and scrutiny within the scholarly accounting literature. This article argues that this is a missed opportunity and that the maturation of blockchain technology may represent as profound a shift in accounting as the emergence and adoption of double‐entry accounting. Abstract : This article argues that the maturation of blockchain technology may represent as profound a shift in accounting as the emergence and adoption of double‐entry accounting.